“FÊ-LO NO IMPULSO DE UM NOBRE CRIME, SENÃO DE SENTIMENTO DA HONRA ULTRAJADA”: a violência contra a mulher nos autos crimes de ferimentos leves da comarca de Bragança-PA (1910-1920) - Filipe de Sousa Miranda (TRF2, 2020)
The present article aims to build some hypotheses regarding the possible contexts in which the violence perpetrated against women by a man her family nucleus was considered a legitimate instrument for maintaining male authority by the Public Justice of the District of Bragança-PA in the second decade of the 20thcentury. The methodology covers the qualitative analysis of two specific cases located in the historical archive of the Bragança-PA District Court of "Autos Crimmes de Injuries" dated of 1912 and 1917. In its course, the text presents the process of constituting the District of Bragança-PA, as well as the form as it was structured in the second decade of the 20th century.Then it goes into the daily functioning of the Correctional Court, the body responsible for judging the crimes of minor injuries. Subsequently, it turns to thenuances of the process of building a final “truth” about the criminal act in the criminal proceedings analyzed, I understand that the version of facts considered true by the Public Justice expresses speeches that denote in which possible scenarios the violence exercised by man against women was not susceptible to legal punishment.